Occurrence of Side Effects in Treatment-Resistant Depression: Role of Clinical, Socio-Demographic and Environmental Characteristics - Levy, Anna; El-Hage, Wissam; Bennabi, Djamila; Allauze, Etienne; Bouvard, Alexandra; Camus, Vincent; Courtet, Philippe; Dorey, Jean-Michel; Etain, Bruno; Fond, Guillaume; Genty, Jean-Baptiste; Holtzmann, Jérôme; et al. (Frontiers in Psychiatry, 2021)
Introduction: Treatment-resistant depression (TRD) is a disabling psychiatric condition characterized by the failure of two antidepressants (ADs). Since the occurrence of side effects (SEs) appears to be one of the main determinants of early discontinuation of pharmacological treatments contributing to a pseudo-resistance, the purpose of this study was to determine the parameters associated with the occurrence of SEs under ADs in a cohort of patients with TRD. Methods: An observational, cross-sectional, multicentre study was carried out using data from the French network of Expert Centers for TRD. For the 108 patients enrolled in the study, the statistical analyses focused on the overall occurrence and on the profile of the SEs (9 categories, 32 items). Results: SEs were influenced by age and sex and were positively associated with the intensity of anxious, depressive and suicidal symptoms, a history of childhood trauma (sexual abuse, emotional abuse and neglect), and negatively associated with self-esteem, and assessment of overall functioning. Conclusion: Using variables accessible in common practice, these results fall within the dynamic of a more tailored approach to medicine that could allow, through integrated pharmacological management, the continuation of antidepressant treatments, and therefore limit the risk of therapeutic failure.